Image repair strategies in the CEO’s tweets regarding AirAsia’s QZ8501 crisis / Grace Lee Si Yunn - Grace Lee , Si Yunn (2019)
In light of the AirAsia QZ8501 crash in December 2014, Tony Fernandes as the Chief Executive Officer, took to Twitter to provide updates on the next course of actions taken by AirAsia as well as convey his thoughts and feelings. Attempts were made by Fernandes to repair his affected image and that of his company to reduce the risk of running losses and also to regain public trust. His effort was crucial as responses to the crisis would be a defining moment in the history of the corporation, determining whether the corporation makes it or breaks. The attempts to repair the sullied reputation are discussed with reference to Benoit’s (2015) image repair theory. It is revealed that Fernandes employed corrective action, bolstering, mortification, denial, and defeasibility. The tweets pertaining to the crisis obtained from Fernandes’s official Twitter account are used as the data and analysed to identify the most salient linguistic features present as well as explain how they realise the function of image repair. The features covered in this work are the personal pronouns ‘I’ and ‘we’ and their possessive determiners, the modal auxiliary ‘will’, the present tense, and the past tense. As manual analysis is conducted, a known limitation is that the interpretation and explanation of the data are subjective due to the influence of the researcher’s prior knowledge. As such, there is a possibility that the understanding and descriptions provided in this work might differ from those of the readers of this work. That this study does not investigate the effectiveness of strategies adopted enables it to be extended in that particular area in the future.